Addressing Self-Injury in Schools, Part 1: Understanding Nonsuicidal Self-Injury and the Importance of Respectful Curiosity in Supporting Youth Who Engage in Self-Injury. (March 2020) - Lloyd-Richardson, Elizabeth E.; Hasking, Penelope; Lewis, Stephen; Hamza, Chloe; McAllister, Margaret; Baetens, Imke; Muehlenkamp, Jennifer
Nonsuicidal self-injury (NSSI) is defined as the deliberate, self-inflicted damage of body tissue without suicidal intent and for purposes not socially or culturally sanctioned. School nurses are often a first point of contact for young people experiencing mental health challenges, and yet they often report they lack knowledge and training to provide care for persons who engage in NSSI. In the first of two parts, this article provides school nurses with a better understanding of NSSI and the distinctions between NSSI and suicidal behaviors, discusses the role of nurses' knowledge and attitudes on their ability to care for their patients' mental health needs, and discusses approaches for developing a respectful, empathic manner for working with and supporting youth who engage in self-injury. Part 2 will offer a strategy for brief assessment of NSSI and reflect on two case studies and their implications for school nursing practice.